2018
DOI: 10.1002/nau.23326
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a heating pad on anxiety, pain, and distress during urodynamic study in the female patients with stress urinary incontinence

Abstract: Using a heating pad for female patients with stress urinary incontinence during a urodynamic study is a simple, economical, and effective therapy that enhances patient comfort and decreases anxiety, pain, and distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
2
8
1
2
Order By: Relevance
“…Heating therapy also resulted in significantly lower anxiety in patients undergoing cystoscopy. These results were consistent with those reported by the cystoscopy [32] and urodynamic studies [33] conducted on women. They reported that heating therapy significantly lowered the state anxiety scores of the study subjects compared to those of the control subjects.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Heating therapy also resulted in significantly lower anxiety in patients undergoing cystoscopy. These results were consistent with those reported by the cystoscopy [32] and urodynamic studies [33] conducted on women. They reported that heating therapy significantly lowered the state anxiety scores of the study subjects compared to those of the control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Heating therapy showed an effective reduction in the score for subjective and objective pain. The results demonstrating relieved pain in the present study are consistent with those of the other two studies on women who underwent cystoscopy in which the experimental group experienced less pain when compared with the control group [32,33]. This pain reduction may have occurred because heating therapy increases blood flow [14,19] and temporarily increases the threshold of pain delivery fibers [43].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In general, UDS is divided into two types that include a noninvasive test called free flowmetry and an invasive test called filling cystometry and pressure-flow study. When invasive UDS is performed, a catheterization will be inserted from the external urethral orifice into the bladder to pump water or contrast media into the bladder and record pressure, which can cause tissue damage and introduction of external pathogens and may also generate discomfort, anxiety, pain, distress, hematuria, and urinary tract infection (UTI) for patients [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%